Association between coping skills and psychological distress in parents of children with learning disabilities referred to the primary school outreach program in selected districts in Kelantan - Nordin, Norazhani (2015)

(untitled)
Background: Children with learning disabilities are one of the vulnerable minority populations in Malaysia. They are at risk of social exclusion and could be denied of their rights. By December 2012 there were 359,203 persons with disability were registered with Department of Social Welfare in which 117,699 were having learning disabilities. This number might not reflect the actual number of Person with Disability in Malaysia since the registration is not compulsory but based on voluntary effort (Islam, 2015). According to the Guidelines for Registration of Person with Disability 2012 Learning Disability is defined as intellectual capabilities that do not conform with biological age and this includes late global development, down syndrome and intellectual disability. It also includes those with autism, attention deficit hyperactivity disorder and specific learning difficulties (2012). From previous studies, parents of children with learning disabilities were more vulnerable to develop psychological distress such as depression, anxiety and stress. This could me due to the stressors they faced in managing their child with disabilities. However, different parents have their own ways of dealing with everyday problems and not all of them will end up having psychological distress. In general, this problem was not addressed adequately as many parents do not report or discuss the difficulties that they experienced when dealing with these problematic child or if they had discussed it with doctors there are no appropriate measures taken to solve their problems. Objectives: The objective of this study is to identify whether parent of children with learning disabilities have psychological distress and to determine whether there is an association between coping skills that they used and psychological distress that they developed. Methods: This is a cross sectional study involving 74 parents (either father or mother) which their child are referred to the Outreach Program in Kelantan, Malaysia. The children who were found to have problems in learning were identified by their teachers and referred to this program for further assessment and evaluation. This study was done in three occasions, 2 screening program done in October and one was done at Psychiatry Clinic HUSM in November for those who missed the program at school were advised to come to clinic for screening. Parents of children with mental disabilities aged 7-12 years old whom were referred to the Outreach program were invited to participate in this study. However those parents diagnosed to have mental illness and who could not communicate well in Bahasa Melayu were excluded from this study. The parents who were identified during the screening program and agreed to participate in this study were given personal information form and two questionnaires which are Depression, Anxiety and Stress Scale 21 (DASS 21) and Brief COPE in Malay version. Results: All of the parents were found to use different combination of coping skills. All of them were found to use problem focused coping skills and 77.0% used emotion focused coping skills. They were also found to have psychological distress in which 29.7% were having depressive symptoms, 44.6% were having anxiety symptoms and 24.3% were having stress. Socio economic status of the parents and the IQ of the disabled child were not associated with psychological distress. Behavioural disengagement coping skills was found to be associated with depression, anxiety and stress (p<0.001, p<0,001 and p=0.003). Ethnicity was found to be associated with anxiety and stress (p=0.026 and p=0.001). Stress was found to be associated with coping skills of self-distraction (p=0.024). Conclusions: Parents of children with learning disability are at risk of developing psychological distress. Less useful coping skills were associated with psychological distress. Socioeconomic status and IQ level are not associated with psychological distress. Association between ethnicity and psychological distress was unable to be confirmed and needed further research. Therefore it is recommended that all parents of children with learning disabilities should be screened for psychological distress and they are given some guidance to cope effectively with their problems.